REVEALING THE IMPACT: META ANALYSIS OF PROBLEM BASED LEARNING MODELS ON IMPROVING COMMUNICATION SKILLS IN SCIENCE LEARNING - Khoviriza, Yessi; Azzahra, Miftahul Zannah; Galadima, Usman; Salsabila, Wanada Siti (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
The purpose of this research is to find out how well the application of the problem based learning model can improve students' communication skills in science subjects. This research uses a meta-analysis method by reviewing several articles in national journals. The data collection technique used is to search for articles that have been published in online journals via Google Scholar. The analysis technique used is miles and huberman. Based on the literature study carried out, it was concluded that the application of the problem based learning model was able to improve students' communication skills in science subjects.